Mn Oxide‐Silver Composite Nanowires for Improved Thermal Stability, SERS and Electrical Conductivity. Issue 29 (30th May 2014) - Pradhan, Mukul; Sinha, Arun Kumar; Pal, Tarasankar
Abstract Redox transformation reaction between aqueous AgNO3 and Mn(CH3COO)2 at low temperature (∼80 °C) has been adopted for industrial‐scale production of uniform Ag–MnOOH composite nanowires for the first time. Varying amounts of incorporated Ag in the composite retain the 1D morphology of the composite. Nanowires upon annealing evolve Ag–MnO2 nanocomposites, once again with the retention of the parental morphology. Just 4 % of silver incorporation in the composite demonstrates metal‐like conducting performance from the corresponding semiconducting material. Transition of MnO2 to Mn2O3 to Mn3O4 takes place upon heat treatment in relation to successive increase in Ag concentrations in the nanowires. The composites offer resistance to the observed oxide transformation. This is evidenced from the progressive increase in transition temperature. In situ Raman, ex situ thermal and XRD analysis corroborate the fact. The composite with 12 % Ag offers resistance to the transformation of MnO2, which is also verified from laser heating. Importantly, Ag nanoparticle incorporation is proved to offer a thermally stable and better surface enhanced Raman scattering (SERS) platform than the individual components. Both the Ag–MnOOH and Ag–MnO2 nanocomposites with 8 atomic % Ag show the best SERS enhancement (enhancement factor ∼1010). The observed enhancement relates to charge transfer as well as electromagnetic effects.